Fault-tolerant design of three-phase dual-buck VSI topologies - Cordeiro, Armando (2019)
This paper presents fault tolerant topologies for the three-phase dual-buck voltage-source inverter (VSI). Using the proposed topologies, increased reliability is obtained, which is fundamental in many safety-critical applications. The solutions intend to achieve fast changing between main and redundant branches through the combination of several power devices. The present study focuses on solutions that can be used to replace the classical two-level three-phase voltage-source inverters to extend the fault-tolerant capacity. Several aspects of failure modes, detection and isolation processes within power electronic converters are discussed regarding the requirements of safety related applications. The theoretical validity of the proposed solution is confirmed by simulation results.